Co-Amorphization of Acemetacin with Basic Amino Acids as Co-Formers for Solubility Improvement and Gastric Ulcer Mitigation - Jiayue Hou; Peixu Zhao; Yanfei Wang; Xiwei Jiang; Qiang Fu (MDPI AG, 2024)
Acemetacin (ACM) is a new non-steroidal anti-inflammatory drug with anti-inflammatory, analgesic, and antipyretic effects. However, the poor water solubility and gastrointestinal side effects limit its use. Recently, the co-amorphous (CAM) strategy has attracted great interest to improve solubility for poorly water-soluble drugs, and basic amino acids have the potential to protect the gastrointestinal tract. In order to develop a highly efficient and low-toxic ACM formulation, we prepared ACM CAM systems, with basic amino acids (lysine, arginine, and histidine) as co-formers, using a cryo-milling method. The solid-state behaviors of the ACM CAM systems were characterized by polarizing light microscopy, differential scanning calorimetry, and powder X-ray diffraction. Fourier transform infrared spectroscopy and molecular docking were carried out to understand the formation mechanism. Moreover, the gastro-protective effects of ACM CAM systems were evaluated in a rat gastric ulcer model. The results demonstrated that the CAM systems improved the dissolution rates of ACM compared with the neat amorphous counterpart. Furthermore, ACM CAM systems are significantly effective in mitigating the ACM-induced gastric ulcer in rats, and the ulcer inhibition rates were almost 90%. More importantly, this study provided a useful method for mitigating drug-induced gastrointestinal damage and broadened the applications of drug-amino acid CAM systems.